Blogging through the music student teaching experience: Developing virtual communities of practice. (June 2014) - Fitzpatrick, Kate R.
Within educational settings, well-developed web-based social networking technologies such as interactive weblogs (blogs) can serve to effectively facilitate and mediate interactions among members of a "community of practice" (Chong, 2008; Wenger, White, & Smith, 2009). The purpose of this study was to investigate the use of an interactive class blog with a group of undergraduate students ( N = 9) enrolled in an American music education student teaching seminar. Specific research questions concerned the alignment of the class blog posts with the three characteristics of the communities of practice model (Wenger, 1998). Analysis of the blog posts, comments, descriptive surveys, and a researcher journal demonstrate that the virtual community did indeed align with the community of practice model in terms of a shared focus on varied aspects of the student teaching experience, a pattern of virtual interactions that demonstrates the formation of a community, and a shared repertoire of resources.